Non-Productive entrepreneurship: A hypothesis on the absence of governance in the BOP settings - Gazi, Mohammad (2017)
Productive entrepreneurial activities may bring economic prosperity and growth to the society, however, the dark side of entrepreneurship can reduce the benefit of entrepreneurship to the society. It is found that alert entrepreneurs under weak institutional development engage more into destructive entrepreneurship. However, the effect of lack of alertness under weak institutional development is yet to discover. Inspired by this gap, the study used comparative perspective under the inductive approach to investigate the indicators of governance of Bangladesh, Brazil and United Kingdom with their global competitiveness indicator, keeping the aim of generating a hypothesis to address possible association between governance and productive entrepreneurial practice to the society. By using descriptive research design and focusing only on secondary data which are quantitative in nature, this study compared entrepreneurial perception, attitude, activity and the indicators of institutions while focusing on both individual-centric and environment-centric factors and conducted a multiple regression model using stepwise method to assess the relation between governance and economic competitiveness of a country. The study generates some hypothesis by explaining that, some indicators of governance may have an association with productive entrepreneurial development, the UK may have managed a balanced institutional development while Brazil and Bangladesh have failed to do so and the lack of entrepreneurial alertness under weak institutional development may result in a new form of non-productive entrepreneurial behavior. However, the propositions made in this study should be evaluated first for checking their validity and no further action should be taken before proving by any empirical research.